Does size matter? Perineometer and digital examination of a model levator hiatus. Issue 5 (11th May 2020) - Tailor, Visha K.; Bhide, Alka A.; Fernando, Ruwan; Digesu, Giuseppe A.; Khullar, Vik
Abstract: Introduction: Evaluation of the female pelvic floor muscles is commonly carried out with digital examination and assigning a modified Oxford scale score or vaginal manometry. Racial differences can influence the size of the levator hiatus (LH) with "black" or African nulliparous women having a significantly larger LH compared to Caucasian women. The aim of this study was to assess the impact of LH size on manometry readings of simulated pelvic floor muscle contractions (PFMCs) using a small and large model LH. Methods: Small and large LH models were created using published data for size. Inflation of a pressure cuff placed circumferentially in the LH model represented a simulated PFMC. The models were examined in a supine position by three examiners and a perineometer twice each at varying simulated PFMC strength. Results: Positive correlation was found between increasing simulated PFMC strength with a higher Oxford score following digital examination and manometry readings for both the small ( r s = .87, r s = .98) and large ( r s = .95, r s = .87) models. There was good to excellent inter and intraobserver correlation for digital assessment of both models. The manometry measurements showed a much larger incremental rise from baseline in the small model compared with the large model ( P < .05). Conclusion: This study demonstrates that perineometer readings are affected by natural variations in LH size and PFMC strength. Therefore improvement to pelvic floor strength cannot be interpreted and measurements cannot be compared with others unless the LH size is known or digital examination is carried out.